COMPLEX OF PROGRAMS FOR ASSESSMENT OF AIR ENVIRONMENT POLLUTION LEVEL - I. V. Kalashnikov (Nauka ta progres transportu, 2019)
Purpose. The work involves the development of numerical models for assessing the level of air pollution in the case of emergencies. Methodology. To describe the process of dispersing in the atmosphere of chemically hazardous substances emitted in emergency situations, we use the three-dimensional equation of the mass transfer of pollutants in the atmospheric air. For the express calculation two-dimensional mass transfer equation is used. Equations of mass transfer take into account the field of wind speed, atmospheric diffusion, the intensity of release of chemically hazardous substances into the atmosphere. For numerical integration of the mass transfer equations, implicit difference schemes are used. The developed complex of programs was created for solving the problems of forecasting the level of atmospheric pollution taking into account the influence of buildings on the formation of pollution zones. In order to take into account the influence of buildings on the formation of pollution zones, the calculation of the velocity field of the wind stream is based on the model of potential flow. Application of this model makes it possible to quickly calculate this field in the presence of obstacles. Findings. The developed mathematical models form the basis of the programs complex and can be applied for carrying out operative calculations of the sizes, intensity of pollution zones, which are formed in the atmosphere during the release of chemical substances in the case of emergency situations on chemically dangerous objects and transport. The developed complex of programs can be realized on computers of small and average power, which allows it to be widely used for solving problems that arise during the development of PLES (plan for liquidation of emergency situations). For practical application of the developed complex of programs, standard input information is required. Originality. The complex of programs for the estimation of the level of air pollution during the release of chemically hazardous substances into the atmosphere is proposed. The program complex can be used to assess the impact of emissions on the risk of chemical damage to people both on the territory of the industrial facility and in the residential area. The basis of the developed complex of programs are numerical models for calculating aerodynamics and mass transfer. Practical value. The developed complex of programs makes it possible to solve the applied problems that arise during the development of PLES for chemically hazardous objects.